A global analysis of the introduction pathways and characteristics associated with non-native fish species introduction, establishment, and impacts - Bernery, Camille; Bellard, Céline; Courchamp, Franck; Brosse, Sébastien; Leroy, Boris (Ecological processes, 2024)
Background The invasion success of introduced freshwater fishes is influenced by many factors, including ecological, species, and socioeconomic characteristics. Most studies that document the importance of these characteristics are conducted at local scales and/or focus on a single step of the invasion process. In this study, we aim to determine the species characteristics, ecological characteristics, and socioeconomic characteristics of non-native freshwater fish invasions. Our assessment was done at the global scale and considers all three steps of the invasion (i.e., introduction, establishment, and impact). For this purpose, we applied generalized linear models to 20 variables collected for 307 non-native species and modeled them as a function of ecological characteristics (i.e., environmental features), species traits (i.e., functional and morphological), and socioeconomic characteristics (i.e., human use and introduction pathways). We considered the number of countries in which each species was introduced, established, or had ecological impacts as a proxy of invasion step success. We also explored the specifics of species introduced through the aquaculture and the ornamental fish trade pathways. Results We found that non-native freshwater fishes with broad diets, high parental care, and multiple introduction pathways are the most widely introduced and established worldwide. The number of countries with impacts reported was best explained by the type of introduction pathway (i.e., aquaculture or fisheries). Moreover, among non-native species introduced through aquaculture, those belonging to Cypriniformes and having broad diets were the most widely introduced and established species. In contrast, the species introduced through the ornamental fish trade pathway belonged to various taxonomic orders but were mainly native to tropical regions. Conclusions Considering several types of factors is important when analyzing the invasion success of freshwater fish and disentangling the different invasion steps. These findings have strong implications for anticipating the profile of species with a high potential to invade many countries.